Numerical Analysis of Thermal Shock Cracking Behaviors of Ceramics Based on the Force-Heat Equivalence Energy Density Principle - Li, Dingyu; Pang, Yong; Lu, Tao; Liu, Zhongshuai; Chen, Shiwei (Frontiers in Materials, 2022)
Thermal shock is one of the main causes for the fracture of ceramic materials due to their inherent brittleness. Aiming to explore the mechanism of thermal shock cracking behavior of ceramics under different thermal shock conditions, a novel temperature-dependent failure criterion of thermal shock fracture of the ceramic materials was deduced based on the force-heat equivalence energy density principle. Combining this failure criterion and the finite element method, the thermal shock cracking behaviors of the thin circular and rectangular ceramic slabs under different thermal shock initial temperature were simulated. Results show that the morphology, periodicity, hierarchy, and number of thermal shock cracks obtained by numerical simulation are in good agreement with the experimental results. These essential characteristics verify the validity of the temperature-dependent failure criterion for thermal shock fracture. Furthermore, the strain energy of tension produced by thermal shock is proved to be the dominated mechanism for thermal shock-induced fracture.